THU0723-HPR A physiotherapy-led in-patient intensive rehabilitation programme for ankylosing spondylitis: follow-up outcomes. (15th June 2017) - Clarke, C; Taggart, P; Monaghan, J; McKnight, J; Cairns, A
Abstract : Background: Physiotherapy and exercise are highly important in the management of Ankylosing Spondylitis (AS). Physiotherapy is delivered to patients with AS in either in-patient or out-patient settings. Knowledge of the effectiveness of an in-patient delivered programme is useful for physiotherapists in assisting patients to achieve their goals. Objectives: To assess the short-term effectiveness of an intensive rehabilitation programme using BASMI and EASI-QOL outcomes, and long-term patient satisfaction and physical activity behaviour and adherence to exercise plan. Methods: Thirty-two AS patients (25 males and 7 females) admitted to an in-patient rheumatology ward underwent a 1 to 2-week physiotherapy-led intensive rehabilitation programme and were then discharged with a home exercise programme. Pre/post rehabilitation BASMI scores were available for 26 patients. The primary outcome measure was the proportion of patients achieving an improvement on BASMI scores at discharge. Secondary outcome measures included improvements in physical activity levels and adherence to home exercise plan for longer than 3 months which was obtained via a postal patient satisfaction and physical activity questionnaire achieving a response rate of 50% (n=16). Results: Improvements in BASMI scores was achieved in 69% of patients (n=18) at the end of the in-patient rehabilitation period. Improvements in EASI-QOL were achieved in 83% of patients (n=15) at the end of the in-patient rehabilitation period. Ninety- four percent of patients (n=15) increased their physical activity levels after discharge, with 81% (n=13) of patients maintaining their home exercise programme for 3 months or more. Thirty-seven percent (n=7) of patients carry out at least 150 minutes of physical activity per week (National Recommended Physical Activity Guidelines is 150 minutes/week of moderate intensity). Conclusions: This recent audit shows the effectiveness of an intensive physiotherapy-led in-patient rehabilitation programme for Ankylosing Spondylitis improving BASMI scores in the short-term and increasing physical activity behaviour over the long-term. Future work will aim to compare demographics and medical treatment differences between improvers and non-improvers. Disclosure of Interest: None declared